The spatial distribution of the reactive iodine species IO from simultaneous active and passive DOAS observations - Seitz, Katja; Buxmann, Joëlle; Pöhler, Denis; Sommer, T.; Tschritter, Jens; Neary, T.; O'Dowd, C.; Platt, Ulrich (Atmospheric chemistry and physics, 2010)
We present investigations of the reactive iodine species (RIS) IO, OIO and I2 in a coastal region from a field campaign simultaneously employing active long path differential optical absorption spectroscopy (LP-DOAS) as well as passive multi-axis differential optical absorption spectroscopy (MAX-DOAS). The campaign took place at the Martin Ryan Institute (MRI) in Carna, County Galway at the Irish West Coast about 6 km south-east of the atmospheric research station Mace Head in summer 2007. In order to study the horizontal distribution of the trace gases of interest, we established two almost parallel active LP-DOAS light paths, the shorter of 1034 m length just crossing the intertidal area, whereas the longer one of 3946 m length also crossed open water during periods of low tide. In addition we operated two passive Mini-MAX-DOAS instruments with the same viewing direction. While neither OIO nor I2 could be unambiguously identified with any of the instruments, IO could be detected with active as well as passive DOAS. The IO column densities seen at both active LP-DOAS light paths are almost the same. Thus it can be concluded that coastal IO is almost exclusively located in the intertidal area, where we detected mixing ratios of up to 29±8.8 ppt (equivalent to pmol/mol). Nucleation events with particle concentrations of 106 cm−3 particles were observed each day correlating with high IO mixing ratios. Therefore we feel that our detected IO concentrations confirm the results of model studies, which state that in order to explain such particle bursts, IO mixing ratios of 50 to 100 ppt in so called "hot-spots" are required.
Gesehen am 21.06.2023